The Determinants of Tax Aggressiveness in Indonesian Coal Mining Companies - Tri Padmawati; Siti Nurlaela; Anita Wijayanti (Jurnal RAK (Riset Akuntansi Keuangan), 2025)
The proposed research aims to evaluate and assess the impact of leverage, capital intensity, profitability, and firm size on tax aggressiveness in Indonesian coal mining enterprises from 2021 to 2023. The sample used in this study comprises coal mining corporations registered on the Indonesia Stock Exchange between 2021 and 2023. The sample was collected using the purposive sampling approach, which resulted in 12 coal mining companies (36 observations) that met the research criteria. This study employs a multiple linear regression analysis, which was conducted using SPSS version 25. The findings indicate that leverage, capital intensity, and profitability have no substantial impact on tax aggressiveness. Furthermore, company size has a significantly positive effect on tax aggressiveness, suggesting that larger companies with more resources are more likely to engage in tax aggressiveness. According to agency theory, the contrast in motivations between management and owners may encourage management to engage in tax aggressiveness to increase firm value.